Edmund Ruffin diaries - Ruffin, Edmund, 1794-1865.
Diaries detailing Ruffin's activities and opinions as an agricultural reformer, anti-unionist, and slavery advocate. Subjects include life on his Virginia estates, Marlbourne Plantation, Hanover County, Va., and Beechwood Plantation, Prince George County, Va.; Virginia state and county agricultural societies; travels and social affairs in the area between Amelia County, Va., and Richmond, Va.; theatrical and other entertainments in Richmond, Va.; religion including Calvinism and Unitarianism; Virginia state and local politics; Confederate and Union politics; and battles and skirmishes, particularly at Charleston and Fort Sumter, S.C., and Manassas, Va. Includes correspondence, fragmentary essays, holograph maps, pamphlets, and clippings.
Plantation owner and publisher.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Keywords: Agriculture; Agriculture -- Virginia; Agriculture -- Virginia -- Societies, etc; Calvinism; Plantations -- Virginia; Religion; Slavery; Theater -- Virginia -- Richmond; Unitarianism; Amelia County (Va.) -- Social life and customs; Beechwood Plantation (Va.); Charleston (S.C.) -- History -- Civil War, 1861-1865.; Confederate States of America -- Politics and government; Fort Sumter (Charleston, S.C.) -- History; Hanover County (Va.) -- Social life and customs; Manassas (Va.) -- History -- Civil War, 1861-1865.; Marlbourne Plantation (Va.); Prince George County (Va.) -- Social life and customs; Richmond (Va.) -- Social life and customs; South Carolina -- History -- Civil War, 1861-1865 -- Campaigns; United States -- History -- Civil War, 1861-1865.; United States -- History -- Civil War, 1861-1865 -- Campaigns; United States -- Politics and government -- 1849-1877.; United States -- Politics and government -- 1861-1865.; Virginia -- Description and travel; Virginia -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865 -- Campaigns; Virginia -- Politics and government -- 1775-1865.; Virginia -- Politics and government -- 1861-1865.; Virginia -- Social life and customs; Plantation owners; Publishers